2020
DOI: 10.1186/s11671-020-03451-5
|View full text |Cite
|
Sign up to set email alerts
|

hGC33-Modified and Sorafenib-Loaded Nanoparticles have a Synergistic Anti-Hepatoma Effect by Inhibiting Wnt Signaling Pathway

Abstract: Delivery of tumor-specific inhibitors is a challenge in cancer treatment. Antibody-modified nanoparticles can deliver their loaded drugs to tumor cells that overexpress specific tumor-associated antigens. Here, we constructed sorafenib-loaded polyethylene glycol-b-PLGA polymer nanoparticles modified with antibody hGC33 to glypican-3 (GPC3 +), a membrane protein overexpressed in hepatocellular carcinoma. We found that hGC33-modified NPs (hGC33-SFB-NP) targeted GPC3+ hepatocellular carcinoma (HCC) cells by speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These carriers enhance drug solubility and stability, thereby improving its efficacy and reducing the adverse side effects that often accompany conventional treatments. For instance, anti-glypican-3, with its significant overexpression in HCC cells, serves as a prime target for sorafenib-loaded polymer nanoparticles[ 8 , 9 ]. GalNAc coupling to asialoglycoprotein, a receptor abundantly expressed on hepatocytes, also emerges as a promising strategy, overcoming hurdles associated with drug resistance and improving the efficiency of liver-specific drug delivery[ 10 , 11 ].…”
Section: Application Of Nanotherapy In Hccmentioning
confidence: 99%
“…These carriers enhance drug solubility and stability, thereby improving its efficacy and reducing the adverse side effects that often accompany conventional treatments. For instance, anti-glypican-3, with its significant overexpression in HCC cells, serves as a prime target for sorafenib-loaded polymer nanoparticles[ 8 , 9 ]. GalNAc coupling to asialoglycoprotein, a receptor abundantly expressed on hepatocytes, also emerges as a promising strategy, overcoming hurdles associated with drug resistance and improving the efficiency of liver-specific drug delivery[ 10 , 11 ].…”
Section: Application Of Nanotherapy In Hccmentioning
confidence: 99%
“…An in vivo HepG2 xenograft mouse model revealed significant inhibition of tumor growth in the presence of targeted NPs loaded with sorafenib compared to non-targeted NPs and free sorafenib [ 196 ]. GC33 has been used as targeting agent of PEG- b -PLGA NPs loaded with sorafenib [ 197 ]. In vitro studies revealed that GPC3-targeted NPs without loading were able to inhibit HepG2 proliferation, increasing the proportion of cells at G1 phase.…”
Section: Nanoparticles Composed Of Organic-based Nanomaterialsmentioning
confidence: 99%
“…These NPs were also able to inhibit the transduction of the proliferation signal dependent on Wnt3a to inhibit epithelial mesenchymal transition, thus attenuating cell migration. In the in vivo study on HepG2 and HUH7 tumor-bearing mice, an inhibition of tumor growth once targeted-NPs loaded with sorafenib were administered, an increase in mice survival, and no toxic effects compared to free drug and untargeted NPs were observed [ 197 ].…”
Section: Nanoparticles Composed Of Organic-based Nanomaterialsmentioning
confidence: 99%
“…The evidence suggests that active targeting of nanomaterials has remarkable advantages in the efficacy of drug delivery. In recent years, with advances in biomarker discovery for liver cancer, many nanomaterials with active targeting ability have improved drug delivery, especially of insoluble drugs, with targeted peptides or antibodies used to confer the active targeting ability and thus improve drug bioavailability and therapeutic effects[ 4 , 5 , 32 ].…”
Section: Efficient Drug Delivery To Improve Treatment Efficacymentioning
confidence: 99%